The grammars of adjudication - Zouhair Ghazzal (Presses de l'Ifpo, 2007)
Most studies on Islamic, Arab, and Ottoman societies and civilizations are trapped into the evidentiary role of the texts that researchers have at their disposal, considerably reducing the role of text and language to a mimetic description of what happened. This book argues that an understanding of social relations primarily implies taking into consideration the textual production of society in terms of the meanings that could be ascribed to the texts themselves, and, second, that the analysi...